GABAergic neurons in the ventral tegmental area represent and regulate force vectors - Qiaochu Jiang; Konstantin I. Bakhurin; Ryan N. Hughes; Bryan Lu; Shaolin Ruan; Henry H. Yin (Cell Reports)
Summary: The ventral tegmental area (VTA), a midbrain region associated with motivated behaviors, contains mostly dopaminergic (DA) neurons and GABAergic (GABA) neurons. Previous work has suggested that VTA GABA neurons provide a reward prediction signal, which is used in computing a reward prediction error. In this study, by using in vivo electrophysiology and continuous quantification of force exertion in head-fixed mice, we identify distinct populations of VTA GABA neurons that exhibit precise force tuning independently of learning, reward prediction, and outcome valence. Their activity usually precedes force exertion, and selective optogenetic manipulations of these neurons systematically modulate force exertion without influencing reward prediction. Together, these findings show that VTA GABA neurons can continuously regulate force vectors during motivated behavior.